Knowledge, attitude, and practices regarding TB among senior management officials of companies with increased silica dust exposure in Lusaka and Southern provinces of Zambia - Mutti, L.; Kagujje, M.; Siameka, D.; Hambwalula, R.; Maimbolwa, M.; Ziko, L. M.; Zimba, K.; Kasese-Chanda, N.; Chimzizi, R.; Mubanga, A.; Muyoyeta, M. (Frontiers in Epidemiology, 2025)
IntroductionA high burden of tuberculosis (TB) complicated by occupational risk factors implies a need for the workplace to develop strategies to reduce workplace incidence of TB.MethodsWe conducted a cross-sectional study to establish the knowledge, attitudes, and practices (KAP) related to TB among senior management officials of manufacturing and construction companies associated with exposure to silica dust. The study was conducted in Lusaka and Southern provinces of Zambia between February and October 2022 using a 28-question multiple-choice self-administered electronic questionnaire. Descriptive statistics were used to determine KAP levels. The total score in KAP was calculated based on correct responses out of a maximum of 17, 7, and 14 points, respectively and categorized into “poor” or “good” using the mean/median. Logistic regression was done to explore the association between characteristics and KAP.ResultsOf 118 participants, 48.3% were aged between 31–40 years, 86.4% were male), and 63.6% represented construction companies. The median/mean KAP scores were 8(IQR 6–10), 3.3 (SD 1.66) and 6.00 (IQR 4–8) respectively. Of the participants, only 47.5% (56/118) had good knowledge, 49.2% (58/118) had good attitudes, and 47.5% (56/118) had good practice scores. Individuals aged over 50 years old, female, and officials from construction companies had higher odds of good knowledge (aOR = 7.8, p = 0.027; aOR = 4.70, p = 0.016 and aOR = 3.45, p = 0.008 respectively) and good attitude (aOR = 14.64, p = 0.021; aOR = 6.51, p = 0.006 and aOR = 3.90, p = 0.006 respectively) Participants working in construction companies had higher odds of good practice (aOR = 2.26, p = 0.048).DiscussionSenior management officials had gaps in knowledge despite having favorable attitudes and practices. Companies must be educated on TB alongside efforts to improve attitudes and practices towards TB in the workplace.